A flap motif in human serine hydroxymethyltransferase is important for structural stabilization, ligand binding, and control of product release - Sakunrat Ubonprasert (2020)
© 2019 Ubonprasert et al. Published under exclusive license by The American Society for Biochemistry and Molecular Biology, Inc. Humancytosolic serine hydroxymethyltransferase (hcSHMT) is a promising target for anticancer chemotherapy and contains a flexible "flap motif" whose function is yet unknown. Here, using size-exclusion chromatography, analytical ultracentrifugation, small-angle X-ray scattering (SAXS), molecular dynamics (MD) simulations, and ligand-binding and enzyme-kinetic analyses, we studied the functional roles of the flap motif by comparing WT hcSHMT with a flap-deleted variant (hcSHMT/Δflap). We found that deletion of the flap results in a mixture of apo-dimers and holo-tetramers, whereas the WT was mostly in the tetrameric form. MD simulations indicated that the flap stabilizes structural compactness and thereby enhances oligomerization. The hcSHMT/Δflap variant exhibited different catalytic properties in (6S)-tetrahydrofolate (THF)-dependent reactions compared with theWTbut had similar activity in THF-independent aldol cleavage of β-hydroxyamino acid. hcSHMT/Δflap was less sensitive to THF inhibition than theWT(Ki of 0.65 and 0.27mM THF at pH 7.5, respectively), and the THF dissociation constant of the WT was also 3-fold lower than that of hcSHMT/Δflap, indicating that the flap is important for THF binding. hcSHMT/ Δflap did not display the burst kinetics observed in the WT. These results indicate that, upon removal of the flap, product release is no longer the rate-limiting step, implying that the flap is important for controlling product release. The findings reported here improve our understanding of the functional roles of the flap motif in hcSHMT and provide fundamental insight into how a flexible loop can be involved in controlling the enzymatic reactions of hcSHMT and other enzymes.